Fa’aaliyah Tahriqah al Tanwiim al Mighnathisii (Hypnoteaching) fii Ta’liim Mahaarah al Qira’ah bi Madrasah Muhammadiyah al Tsanawiyah Malang - Alizar, Mahfud; Sutaman, Sutaman; Al Anshory, Abdul Muntaqim (AL-WARAQAH Jurnal Pendidikan Bahasa Arab, 2024)
The purpose of learning maharoh qiroah is to familiarize students with understanding what they read from books or other things, they can understand it properly and quickly without difficulty. However, in maharoh qiroah learning there are several obstacles including learning using which is boring for students, students have difficulty understanding the material being taught. To overcome this problem, researchers offer maharoh qiroah teaching using hypnoteaching, in order to create dynamic and intertwined teaching, and increase their enthusiasm to get the desired results. This aims of this research to find out how yelling, magic questions, and emotional clocks are applied using the hypnoteaching method in maharoh qiroah learning at MTs Muhammadiyah 2 Malang; and to find out how far the effectiveness of using the hypnoteaching method is in learning maharoh qiroah at MTs Muhammadiyah 2 Malang. This research is quantitative and qualitative approaches, and data collection uses pre-test and post-test, direct observation, and interviews. In analyzing the data, the researcher used an independent sample test t-test. The results of this study are that hypnoteaching can to make students feel confident in receiving the material, to increase students' enthusiasm in learning, to create rapprochement between teachers and students, and to create a positive learning environment: encourage students to participate actively in learning, can increase the joy and enthusiasm of students in learning, and make the learning atmosphere fun; The magic questions can provide student learning solutions, provide psychological encouragement to students, and direct student learning goals; The emotional hours can help maintain calm during learning, and make students disciplined in participating in learning; Whereas for the Independent Sample Test results obtained significant results (0.00) smaller than (0.05), these results indicate that the hypnoteaching method is able to improve learning outcomes of maharoh qiroah. And from the N-Gain Score test, the results for the experimental class were 50,59%, so it was found to be effective